IDDF2022-ABS-0175 Incidence, epidemiology and outcomes of acute allograft rejection following liver transplantation – an australian single centre study. (2nd September 2022) - Tang, Lauren; Chetwood, John; Powter, Elizabeth; McKenzie, Catriona; Crawford, Michael; Bowen, David; Strasser, Simone; McCaughan, Geoffrey; Liu, Ken
Abstract : Background: Liver transplantation (LT) is complicated by graft rejection in 15–30% of cases. The epidemiology and outcomes of graft rejection have not been well-described in the Australian setting. Methods: We retrospectively studied consecutive adults who underwent deceased-donor LT 2015- 2019. Liver biopsy reports were reviewed, and only the first instance of biopsy-proven rejection was analysed. Results: During the study period (median follow-up 55 months [IQR 41–72]), 339 patients underwent LT (68% male, median age 56 years [IQR 48–60], median MELD score 19 [IQR 14–25] at time of LT). Main indications for initial transplant were: decompensated cirrhosis (65%), HCC (26%), and acute liver failure (7%). Induction immunosuppression involved tacrolimus (97%), corticosteroids (65%) and/or basiliximab (57%). Biopsy-proven rejection occurred in 118/339 recipients (35%): 111/118 (94%) acute T-cell mediated; 7 (6%) antibody-mediated. The median time from LT to rejection was 40 days (IQR 13–230). The cumulative rates of rejection at 1, 3, 6, 12 and >12 months were 16%, 20%, 24%, 29%, and 35%, respectively. The histological severity of rejection was mild in 50%, moderate in 41% and severe in 12%. Independent predictors of rejection post-LT on multivariable analysis were: recipient age (aOR 0.974, P =0.036), donation after circulatory death graft (aOR 2.904, P =0.027) and cold ischaemia time (aOR 1.145, P =0.031). The majority (85/118, 72%) of patients were treated in hospital. Of these, 51/85 (81%) received one course of pulse intravenous methylprednisolone, 20 (24%) received ≥2 courses and 14 (16%) required anti-thymocyte globulin (n=7), IVIg (n=8), and/or plasmapheresis (n=8) or urgent retransplantation (n=3). Development of rejection did not impact long-term graft survival or patient survival compared to those without rejection (IDDF2022-ABS-0175 Figure 1. Graft Survival) (IDDF2022-ABS-0175 Figure 2. Patient Survival). Conclusions: In this Australian study, allograft rejection after LT occurred in 35% with independent risk factors of younger recipient age, donation after circulatory death graft, and increased cold ischaemia time. The majority of cases responded to corticosteroid treatment. Long-term graft and patient survival were not impacted.